Labor Skills and Foreign Investment in a Dynamic Economy : Estimating the Knowledge-Capital Model for Singapore - Chellaraj, Gnanaraj; Maskus, Keith E.; Mattoo, Aaditya (2012)
Singapore is an interesting example of how the pattern of foreign investment changes with economic development. The authors analyze inbound and outbound investment between Singapore and a sample of industrialized and developing countries over the period 1984-2003. They find that Singapore s two-way investment with industrialized nations has shifted into skill-seeking activities over the period, while Singapore s investments in developing countries have increased sharply and become concentrated in labor-seeking activities. Singapore s increasing skill abundance relative to all countries in the sample accounted for 41 percent of average inbound stocks during the period, that is, US$18 billion annually; the corresponding figure for outbound stocks was 40 percent, that is, US$5.51 billion annually.